Design Platform Financial Aggregator in Agriculture - Arsi Amallah Binhaq (APIC, 2019)
Investment in agriculture is an important factor to increase country’s revenue. At this time, investment in agriculture was decreased because of low interest from investor to join the agriculture project. This problem can be minimized by giving some information that relevant with investor’s need. Financial Aggregator is the one paradigm for collecting data to get some insight for financial transaction. This paradigm supported by technique called web scraping. Concept financial aggregator can be delivered by designing platform that contain accurate information for investor and farmer to increase their productivity especially in agriculture project. This platform will give analysis data of some agriculture startup and transform it into information that help investor to choose best investment in agriculture.